Tribology-Related Researches at Faculty of Mechanical Engineering, Universiti Teknikal Malaysia Melaka (UTeM) - Abdollah, Mohd Fadzli bin; tamaldin, noreffendy; Amiruddin, Hilmi; Mohd Zamberi, Mahanum; Rody, M. Z. M; Mat Kamal, Sushella Edayu (2012)
The establishment of the Faculty of Mechanical Engineering (FME), Universiti Teknikal Malaysia Melaka (UTeM) was officially approved by the Ministry of Education Malaysia on June,22 2001. FME is located at the Industrial Campus, UTeM. Centre for Advanced Research on Energy (CARE) is one of the Centre of Excellence driven by management and knowledge of FME. The center acts as a base for bringing together people from a variety of disciplines to work on specific problems of interest. These problems may be defined within the Center without particular knowledge of funding, drawing upon strengths of the people involved.